An investigation of the role of product, place, promotion and price (4Ps) in market basket analysis: a case study of retail shops in Gweru Zimbabwe - Musungwini, Samuel; Zhou, Tinashe G. (2016)
Market basket analysis is a technique that discovers relationships between pairs of products purchased together. The technique can be used to uncover interesting cross-sells and related products. The purpose of this paper is to come up with a proposal on a research survey aimed at investigating the role of Product, Place, Promotion and Price (4Ps) in Market Basket Analysis (MBA) and establishing how the 4Ps can be applied as a tool for competitive advantage in the retail sector in Zimbabwe. To conduct this study the researchers propose to carry out observations, and examine transactions of customers for retail shops in Gweru. A survey questionnaire will also be used to elicit data. Finally the researchers will then evaluate the empirical data and compare it with literature evidence to reveal relationships. It is hoped that the results of the study will provide recommendations for the retail sector in Gweru about changes that need to be adopted in order to attract more traffic into their stores and increase the size and value of the basket purchases.